Worldwide variation of adherence to the Mediterranean diet, in 1961-1965 and 2000-2003 - Silva, Rui (2009)
Objective: The present study aimed to analyse the worldwide trends of adherence to the Mediterranean diet (MD), in 1961-1965 and 2000-2003. Design: Data were obtained from the FAO food balance sheets in two periods: 1961-1965 and 2000-2003. In order to have a sample from across the world, forty-one countries were selected. The average of available energy for different food groups was calculated for all selected countries. These values were used to evaluate the adherence to the MD through a variation of Mediterranean Adequacy Index (MAI). Results: The majority of the forty-one countries in this study have tended to drift away from a Mediterranean-like dietary pattern. Mediterranean Europe and the Other Mediterranean country groups suffered a significant decrease in their MAI values. The Mediterranean European group, especially Greece, experienced the greatest decrease in MAI value. In both periods, the Other Mediterranean countries showed the highest MAI values. In an analysis by countries, Iran had the highest increase in MAI across the time periods, and Egypt occupied the first place in the ranking in 2000-2003. The Northern European group was the only one that registered an increase in MAI, although this was not statistically significant. Conclusions: Many countries in the Mediterranean basin are drifting away from the Mediterranean dietary pattern (MDP). However, countries in Northern Europe and some other countries around the world are taking on a Mediterranean-like dietary pattern. The Other Mediterranean countries have the closest adherence to the MDP, currently and in the 1960s. Nutrition policy actions to